PENINGKATAN KETERAMPILAN BERBICARA MENGGUNAKAN MEDIA GAMBAR BERSERI DI KELAS III SEKOLAH DASAR - Estika, Vera; Halidjah, Siti; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to improve the skills of speaking using the medium of image of the students of public elementary school in Pontianak city. This research uses descriptive method, form of classroom action research, and collaborative nature. The procedures used there are 4 stages of the planning stage, the stage of implementation, the stage of observation, and the stage of reflection. Where the research took place in public elementary school Pontianak City 12, class III which amounted to 23 students who serve as the subject. The techniques, and techniques of document observation with the instrument of collecting data in the form of observation sheet. The study was conducted in 3 cycles with each cycle of two meetings. The results of the study 1) the ability of teachers to design learning on the first cycle average score 3,04, cycle II average score 3,27, and cycle III average score 3,84. 2) the ability of teachers to implement learning from cycle I average score 2,98, cycle II average score 3,22, and cycle III average score 3,65. 3) studens’ speaking skill in cycle I with average value 53,78, in cycle II with mean value 76,13, and at cycle III with the mean value 83,69. Thus, researchers using the medium of serial images can improve the students’ speaking skills in the third grade of public elementary school 12 Pontianak City. Keywords: Improvement, Speech Skills, Using the Collectible Media.